Letter (copy) : International conference: London - 10-11 March - Citrine, Walter, 1887-1983
022_0015-001 WMC/EAB/510 International. 3rd March 1937. Sir R.R. Scott, K.C.B., C.S.I., I.S.O., Home Office, WHITEHALL. S.W. 1. Dear Sir Russell, INTERNATIONAL CONFERENCE: LONDON - 10-11 MARCH. With further reference to our conversation regarding the above Conference, I have communicated to the Secretary of the International Federation of Trade Unions the point of view of your Department in regard to the delegates who will be coming to London to take part in the Conference and Demonstration. I have informed him that in view of the statement made in the House of Commons on the 11th February last by Mr. G.W. Lloyd, M.P., it has been made very clear that it will not be possible for the Home Office to allow any person, admitted to this country to take part in the Conference, to indulge in propaganda meetings. I have also informed him that I have given an assurance that the Demonstration, which is to be held on Wednesday evening, 10 March, will be solely for the purpose of getting support for the International Solidarity Fund, and that persons appointed by their organisations to attend the Conference should be clearly informed on these points. In order to avoid any possibility of difficulties at the Ports, it has been arranged that each Delegate will be provided with a Credential Form, bearing his name, the name of his Organisation, and his signature, which he will show to the immigration officers upon arrival at the Ports. I am enclosing herewith twelve blank copies of the Credential Form which has been issued in order that you may, should you consider it desirable, circulate them among the immigration officers concerned. With many thanks for your assistance, I am, Yours sincerely, General Secretary. 12 Credential Cards. 292/946/22/14